2011
DOI: 10.1002/jssc.201000873
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated monolithic column for CEC

Abstract: In order to overcome the drawbacks associated with particle-based fluorinated stationary phases, a fluorinated cationic monolith was successfully synthesized by the in situ copolymerization of a 45% monomer mixture and 55% porogens with thermal initiation using 0.1% initiator with respect to the monomer mixture. The monomer mixture was composed of perfluorododecyl acrylate (49.75%), ethylene dimethacrylate (49.75%), and 0.5% of the quaternary amine acrylic monomer supporting an anodal electroosmotic flow. A te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…), whereas column C (30% monomer mixture) possessed the best permeability with only 850 psi at a flow rate of 6 μL/min (200 μm i.d.× 100 mm, mobile phase: ACN). This was because the density of the monolith skeleton increased with decreasing through‐pore size as the ratio of the monomer stock solution increased .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…), whereas column C (30% monomer mixture) possessed the best permeability with only 850 psi at a flow rate of 6 μL/min (200 μm i.d.× 100 mm, mobile phase: ACN). This was because the density of the monolith skeleton increased with decreasing through‐pore size as the ratio of the monomer stock solution increased .…”
Section: Resultsmentioning
confidence: 99%
“…Since it was reported that the 1‐octanol played an important role on the preparation of a polymer monolithic column , the column preparation was initially examined with a polymerization mixture consisting of 70% porogens (40% 1‐propanol, 40% 1‐octanol, and 20% 1‐dodecanol) and 30% monomer mixture. 1‐Propanol acts as a microporogen that would affect the surface area, and 1‐dodecanol acts as a macroporogen that would affect the through‐pore size distribution , whereas 1‐octanol would reduce the size of voids and increase the surface area . The ratio of microporogen (1‐propanol) to macroporogen (1‐octanol and 1‐dodecanol) was kept constant at 40:60, and the amount of 1‐octanol was varied from 20 to 40%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No uorous analyte was used. Choodum et al 23 thermally fabricated a uorous monolith from 1H,1H,2H,2H-peruorodecyl acrylate (PFDA), EDMA, and [2-(methacryloyloxy) ethyl]trimethylammonium methyl sulfate (METAM), the latter being a positively charged component to generate electroosmotic ow for CEC. Polar phenolic compounds (hydroquinone, phenol, and catechol), nonpolar aromatic hydrocarbons (benzene, toluene, and xylene) and only one uorine-containing compound, tau-uvalinate, were separated by the FPPM column.…”
Section: Introductionmentioning
confidence: 99%